Parents' Perceptions of the Challenges to Helping Their Children Maintain or Achieve a Healthy Weight - Sara N. Bleich; Mary T. Gorski Findling; Robert J. Blendon; Eran Ben-Porath; Gillian K. SteelFisher (Hindawi Limited, 2019)
Introduction. Parents play a critical role in their children's weight. This paper examines parents' perceptions about the challenges to helping their kids maintain or achieve a healthy weight. Methods. We analyzed data in 2017 from a U.S. telephone poll conducted during October-November 2012 among parents or caregivers of children aged 2-17 years using a nationally representative sample of households. It included 667 White, 123 Black, and 167 Hispanic parents. Multiple logistic regressions were used to examine parent perceptions about the individual- and environmental-level challenges to helping their children maintain or achieve a healthy weight. Results. Overall, 45% of children have parents who reported challenges helping the child eat to maintain or achieve a healthy weight, and 35% have parents who reported challenges for exercise. According to parents, most children consumed snacks between 3 pm and bedtime during the school week (83%), and 63% of those children had an unhealthy snack. Parents did not express much concern about unhealthy snacks; 80% of children had parents who said that they did not mind since their child generally ate healthy food. Children with Hispanic and Black parents were more likely than those with White parents to have parents reporting environment challenges, such as unhealthy foods in schools. Conclusions. Helping children maintain a healthy weight through diet is a problem for many parents, regardless of their race or ethnicity. Differences by race/ethnicity in parent perceptions of food environment challenges to helping their child maintain or achieve a healthy weight suggest possible areas for future interventions.